Removal of sulphide using phytoremediation process - Syarifah, Abd Rahim; Koh, Rui Shuan (Elsevier Ltd, 2018)
Rapid development in social and economic area has created a serious environment contamination of soil and groundwater. The discharge of toxic material and contaminant has increased significantly during the last few years. Hence, a cost-effective and environment friendly alternative method such as phytoremediation process is fulfilling those characteristics. In this study, the semi-batch phytoremediation process, consist of adding a similar total amount of sulphide content to the Scirpus grossus plants over a seven-day period of time was investigated. Throughout the experiment, the plants growth was observed physically to identify the ability of the plant to survive and resist the sulphide contaminant. The sulphide concentration for each sample was analysed and the percentage of the withered plants was calculated. The results revealed that the percentage of the withered leaves increase throughout the semi-batch process. It was found that the percentage of sulphide removal reaches up to 70%. The finding suggested that the phytoremediation using Scirpus grossus plants is possible to be used for sulphide removal